Valuing less and guarding more: Consumption stewardship in restricted contexts. (21st May 2022) - Barrios, Andrés; Blocker, Christopher P.; Upadhyaya, Shikha
Abstract: This paper advances the conceptual understanding of consumption stewardship, defined here as a moral commitment to safeguard, nurture and use consumption resources to create consumer value. We delineate consumption stewardship from related consumption variables and articulate its underlying assumptions, conceptual distinctiveness and application areas. To create new theoretical and practical insights, the paper explores how consumption stewardship unfolds when a person enters into and lives in restricted consumption. A 2‐year qualitative study, which included observation, casual conversations, and interviews, was implemented. Findings illustrate the nature and trajectory of consumption stewardship across latent, vigilant, submissive and shared modes. Our conceptual development of consumption stewardship and empirical evidence of the homeless experiences makes two main contributions. First, we show how the demands of stewarding material objects operate as a powerful determinant for individual (re)valuation of various possessions. Second, we identify how consumption stewardship drives different ways of consumption for value seeking. Findings offer insights for debates in the marketplace about protecting one's possessions, policies around consumption adequacy and social services' role for addressing space‐related needs of vulnerable consumers.